2019
DOI: 10.18203/2320-1770.ijrcog20192421
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in antenatal women

Abstract: Background: Vitamin D has an increasingly recognised repertoire of non-classical actions, such as promoting insulin action and secretion, immune modulation and lung development. It therefore has the potential to influence many factors in the developing fetus. Several studies reported the relationship between maternal vitamin D deficiency and adverse maternal and fetal outcomes including gestational diabetes, preeclampsia, preterm labour, low birth weight and increased rate of caesarean section. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…23 In a study by Chandel et al, it is reported that majority of vitamin D deficient subjects were <30 years of age. 22 In contrast to this, our study indicated that age groups older than 30 years had a higher prevalence of vitamin D deficiency and insufficiency. In our study, 78% of women over 30 and 58% of women under 30 were impacted by the condition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…23 In a study by Chandel et al, it is reported that majority of vitamin D deficient subjects were <30 years of age. 22 In contrast to this, our study indicated that age groups older than 30 years had a higher prevalence of vitamin D deficiency and insufficiency. In our study, 78% of women over 30 and 58% of women under 30 were impacted by the condition.…”
Section: Discussioncontrasting
confidence: 99%
“…This high incidence in this study might be a result of urban dwellers spending more time indoors and participating in less outside activities due to air pollution, which also reduces exposure to sunshine. 21 For women of childbearing age, two to three sessions of roughly 10-15 minutes of sun exposure each week are strongly advised to absorb an adequate quantity of vitamin D. 22 Even 11.1 hours of total body exposure to sunlight per week, according to a recent study among Hawaiians, was insufficient to halt the development of "low vitamin D status." 23 In a study by Chandel et al, it is reported that majority of vitamin D deficient subjects were <30 years of age.…”
Section: Discussionmentioning
confidence: 99%